PPERCEPTION OF MADURA DA’I ABOUT EARLY MATCH (Phenomenology Study in Madura, Indonesia) - Rifa'i, Mohammad (UIN Sumatera Utara, 2023)
Madurese people are known as people who have a habit of pairing children at an early age, and some are even toddlers or babies still in the womb who have been booked for amatch. Early match in Madura is one of the causes of early marriage, and then it causes of school dropouts. This needs attention from influential person in the people, one of is Da'i. The da’ipercetion of these social realities are important so that they can provide understanding to the Madurese people about the early match well.This study aims to know: 1) perception of Madura da’i about early match, and 2) typology of Madura da’i on early match. To achieve these objectives, the author uses qualitative-field methods by collecting data through observation, interviews and documentation. While for data analysis, the author uses the phenomenology theory.The result of this study: Madura da’i perceive about early match as i'tikad (effort) that is an effort of parents who need to protect and worry to their children. Madura da’i also perceive that early match in Madura contains values of Islam; those are: (a) minimizing of approaching zina, (b) inviting to follow sunnah, and (c) inviting to keep the family relationship. Beside that, there are two typologies of Madura da’i about early match; first type is da’i who agrees to early match; second type is da’i who disagrees to early match.